2011
DOI: 10.1149/1.3536477
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Thick Polycrystalline AlN Layers by HTCVD

Abstract: International audienceThick polycrystalline AlN layers were grown at low pressure using high temperature chemical vapor deposition (HTCVD). The experimental setup consists of a graphite susceptor heated by an induction coil surrounding a vertical cold wall reactor. The reactants used were ammonia (NH(3)) and aluminum chloride (AlCl(x)) species formed in situ via chlorine (Cl(2)) reaction with high purity aluminum wire. AlN films were deposited on a 55 mm diameter graphite susceptor between 1200 and 1600 degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 37 publications
(70 reference statements)
5
7
0
Order By: Relevance
“…All the HT-AlN samples grown using the NL deposition temperature of 650 • C are polycrystalline and show a (1011) semi-polar It is important to note that direct growth (without NLs) of AlN films at 1200 • C on sapphire c-plane substrates with the same experimental conditions leading to the growth of semi-polar oriented polycrystalline AlN layers as already observed in the previous work at high growth rate [30]. The introduction of NLs prior to HT-AlN films for wetting the substrate surface, producing the nucleation sites and acting as a buffer layer to accommodate the lattice mismatch between sapphire and AlN films certainly promote AlN epitaxial growth on sapphire.…”
Section: X-ray Diffraction and Surface Morphology Studiessupporting
confidence: 70%
See 1 more Smart Citation
“…All the HT-AlN samples grown using the NL deposition temperature of 650 • C are polycrystalline and show a (1011) semi-polar It is important to note that direct growth (without NLs) of AlN films at 1200 • C on sapphire c-plane substrates with the same experimental conditions leading to the growth of semi-polar oriented polycrystalline AlN layers as already observed in the previous work at high growth rate [30]. The introduction of NLs prior to HT-AlN films for wetting the substrate surface, producing the nucleation sites and acting as a buffer layer to accommodate the lattice mismatch between sapphire and AlN films certainly promote AlN epitaxial growth on sapphire.…”
Section: X-ray Diffraction and Surface Morphology Studiessupporting
confidence: 70%
“…along z) are thus a clear indication of their non-polar or semi-polar orientation. A similar approach has been successfully used for the Raman analysis of polycrystalline AlN films grown by HTCVD [30] and AlN fibers grown by sublimation growth [39]. The E 2 (h) and A 1 (LO) phonon modes, characteristic of (0 0 0 1) planes have been observed in the smooth surface (A) of Fig.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 99%
“…About non-polar PVT seeds, these first results are very promising. As expected from our previous study [14], it seems that non-polar AlN epitaxial growth at high growth rate is stabilized at the expense of (0001) polar epitaxial growth using HTCVD process in the Al-N-Cl-H system. Characterizations of those homoepitaxial AlN layers such as crystalline quality and defects structure still are under investigation and will be published elsewhere.…”
Section: Resultssupporting
confidence: 86%
“…Recent studies on the growth of polycrystalline AlN layers by HTCVD revealed that the non-polar plane (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) normal to the substrate seems to correspond to the most stable orientation of facetted AlN layers grown at both high temperature and high growth rate [14]. This observation suggests that, in these operating conditions, non-polar AlN epitaxial growth at high growth rate could be stabilized at the expense of (0001) polar epitaxial growth using HTCVD process in the Al-N-Cl-H system [14]. From our knowledge, the AlN homoepitaxial growth on polar and non-polar bulk AlN substrates by HTCVD or HVPE has not been previously reported.…”
mentioning
confidence: 99%
“…The HTCVD set-up consists of a graphite susceptor heated by induction in a water-cooled vertical cold-wall quartz reactor working at low pressure [17][18][19]26,27]. Schematics of the CVD reactor are given in Refs.…”
Section: Methodsmentioning
confidence: 99%